Detection and genetic characterization of the novel torque teno virus group 6 in Taiwanese general population. Issue 11 (3rd November 2021) - Hsiao, Kuang-Liang; Wang, Li-Yu; Cheng, Ju-Chien; Cheng, Yu-Jung; Lin, Chiung-Ling; Liu, Hsin-Fu
Abstract : Torque teno virus (TTV) is one of the most common human viruses and can infect an individual with multiple genotypes chronically and persistently. TTV group 6 is a recently discovered phylogenetic group first isolated from eastern Taiwan indigenes, but whether the TTV group 6 was also prevalent in the general population still unknown. One hundred and three randomly collected blood samples from general population and 66 TTV positive DNA samples extracted from Taiwan indigenes were included. A group-6-specific PCR was developed for re-screen over TTV positive samples. Two TTV group 6 positive samples from general population were cloned and sequenced for identifying mix-infected TTVs and confirming their classification by maximum-likelihood and Bayesian inference phylogeny. TTV group 6 can be detected in 4.5% (4/89) and 7.6% (5/66) of TTV positive samples from Taiwanese general population and eastern Taiwan indigenes, respectively. Sample VC09 was mix-infected with TTV groups 3 and 6. Sample VC99 was mix-infected with TTV groups 3, 4 and 6. A highly diverse triple overlapping region was observed, which may represent a unique phenomenon of TTV. The group-6-specific PCR can successfully detect TTV group 6. TTV group 6 may be prevalent worldwide regardless of the geographic region and/or ethnic groups.